A survey of adult and pediatric epilepsy surgery in the United Kingdom. Issue 5 (29th March 2013) - Neligan, Aidan; Haliasos, Nik; Pettorini, Benedetta; Harkness, William F. J.; Solomon, Juliet K.
Summary All consultant epilepsy neurosurgeons were asked to prospectively record all epilepsy surgery procedures carried out at their center between April 2010 and March 2011. Figures were compared to a previous survey completed in 2000. Of a total of 710 procedures, temporal lobe surgery was the most common resective surgery. Although extratemporal lesional surgery was less common, vagus nerve stimulator (VNS) implantation accounted for almost half the procedures. The numbers for all surgical procedures, with the exception of VNS implantations, had decreased. This decrease may represent a global rather than a regional phenomenon. Further longitudinal multinational data on epilepsy surgery is required to confirm or refute this theory.